1981
DOI: 10.1002/1097-4679(198104)37:2<276::aid-jclp2270370208>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors that predict reaction to abortion

Abstract: Investigated demogra hjc and psycholo 'cal factors related to positive or negative reactions to Lgal abortions pezrmed during the first trimester of pregnancy in 62 females in an urban southern community. Results s est that the social context and the degree of support from a series of s a a n t persons rather than demographic variables were most predictive of a positive reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 6 publications
2
26
0
1
Order By: Relevance
“…The associations observed could suggest that women who have recently undergone an abortion are more prone to substance use than women who have recently delivered a child due to negative emotions incurred from the abortion. Existing data do indicate that women with a history of abortion, compared to women without such a history, are more inclined to experience negative emotions (Gould 1980;Franco et al 1989;Moseley et al 1981). This interpretation is supported by the fact that substance use during the initial pregnancy (alcohol, tobacco) as well as ever having been treated for substance use were not systematically related to the choice to abort.…”
Section: Discussionmentioning
confidence: 98%
“…The associations observed could suggest that women who have recently undergone an abortion are more prone to substance use than women who have recently delivered a child due to negative emotions incurred from the abortion. Existing data do indicate that women with a history of abortion, compared to women without such a history, are more inclined to experience negative emotions (Gould 1980;Franco et al 1989;Moseley et al 1981). This interpretation is supported by the fact that substance use during the initial pregnancy (alcohol, tobacco) as well as ever having been treated for substance use were not systematically related to the choice to abort.…”
Section: Discussionmentioning
confidence: 98%
“…Demographics have historically been investigated in attempts to determine the causes and consequences of adolescent pregnancy (Chilman, 1983 ;Mott & Marsiglio, 1985) as well as adolescent abortion (Adler et al, 1990 ;Martin, 1973 ;Moseley, Follingstad, Harley, & Heckel, 1981). For example, Miller, Higginson, McCoy, and Olson (1987) found that family configuration is related to the sexual attitudes and behaviors of the adolescents, even when factors such as age, sex, race, religion, church attendance, and parent education are controlled (see also Forste & Heaton, 1988 ;Keith, McCreary, Collins, & Smith, 1991 ;Miller & Moore, 1990).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Studies by Moseley, Follingstad, Harley, and Heckel (1981), Robbins (1984), and Bracken (1978) found that perceived amount of support by the woman's significant other was an important determinant of her psychological reaction to the abortions also including the strength of the relationship. Moseley et al (1981) administered pre-and post-test measures of depression, anxiety and hostility, and difficulty of decision making to 62 women.…”
Section: Social V W L E Smentioning
confidence: 99%
“…Moseley et al (1981) administered pre-and post-test measures of depression, anxiety and hostility, and difficulty of decision making to 62 women. While perceived support was important, they found that if a woman's partner was a casual acquaintance, the decision was easier than if he were a spouse or fiance.…”
Section: Social V W L E Smentioning
confidence: 99%